1978
DOI: 10.1094/phyto-68-383
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sclerotium Populations of, and Apothecium Production by, Sclerotinia sclerotiorum

Abstract: Sclerotium populations of Sclerotinia scierotiorum were germinated sclerotium in both crops. An apothecium variable during this 3-yr study; however, sclerotia did not continued to produce ascospores in the field for about 7 days. accumulate in increasing numbers in fields planted to Apothecium production was less beneath the open bush susceptible dry edible bean (Phaseolus vulgaris) cultivars canopy of dark red kidney Charlevoix and the upright semidespite annual white mold epidemics. Populations ranged vine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
16

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 0 publications
6
100
0
16
Order By: Relevance
“…According to Steadman (1983), a single sclerotium can produce over 2,000,000 ascospores in a period of 10 days. These results show the great ability of S. sclerotiorum to infect, even from low inoculum density, as also demonstrated in a study by Schwartz and Steadman (1978), where only 0.2 sclerotia per kg of soil provided 46% incidence of white mold in beans. This emphasizes the need to reduce sclerotia production by using fungicides in order to reduce the inoculum present in the soil, thereby helping to control the disease in future crops.…”
Section: Nssupporting
confidence: 85%
See 1 more Smart Citation
“…According to Steadman (1983), a single sclerotium can produce over 2,000,000 ascospores in a period of 10 days. These results show the great ability of S. sclerotiorum to infect, even from low inoculum density, as also demonstrated in a study by Schwartz and Steadman (1978), where only 0.2 sclerotia per kg of soil provided 46% incidence of white mold in beans. This emphasizes the need to reduce sclerotia production by using fungicides in order to reduce the inoculum present in the soil, thereby helping to control the disease in future crops.…”
Section: Nssupporting
confidence: 85%
“…It is important to achieve good penetration of the spray in the canopy, and adequate wetting of the lower and middle third of the crop, thereby mainly affecting the flowers during the soybean flowering period, which are the initial energy source for white mold infection, coinciding with the release of ascospores by the pathogen (ABAWI, et al, 1975;SCHWARTZ;STEADMAN, 1978;MUELLER et al, 2002). However, the continuous use of the same active ingredient can cause resistance to the pathogen, as shown with carbendazim (YIN et al, 2010) and methyl thiophanate (MUELLER et al, 2002); consequently, it is important to rotate the different active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting carpogenic germination of S. sclerotiorum have been described in many papers (Schwartz and Steadman 1978;Caesar and Pearson 1983;Dillard et al 1995;Sun and Yang 2000;Matheron and Porchas 2005;. The most important are moisture and temperature.…”
Section: Pathogen Biologymentioning
confidence: 99%
“…According to the Suzui and Kobayashi (1972), 3.2 sclerotia per m 2 may cause 95% infection of kidney bean in the field whereas Schwartz and Steadman (1978) showed that the minimum number of sclerotia to incite a moderately severe disease of dry edible bean (Phaseolus vulgaris) is 0.2 sclerotia/kg of soil.…”
Section: Disease Developmentmentioning
confidence: 99%
“…The disease leads to watery rot of fully grown cabbage heads in the field, during post harvest operations and storage (Hudyncia et al, 2000). This pathogen is recognized as important due to its worldwide distribution (Adams and Ayers, 1979;Purdy, 1979), its wide host range (Schwartz et al, 1977;Purdy, 1979;Boland and Hall, 1994) and the difficulties encountered in controlling the diseases it causes (Lumsden, 1979;Steadman, 1979). Sclerotia are the primary survival structures of the pathogen (Korf and Dumont, 1972).…”
Section: Introductionmentioning
confidence: 99%